Management and organisational behaviour - Mullins, Laurie J. (Harlow : Financial Times Prentice Hall, 2010)
Presenting a managerial approach to the study of organisational behaviour, with an emphasis on improving working performance through a better understanding of human resources, this book contains summaries, review questions and assignments.
Includes Internet access.
Includes bibliographical references and index.
Keywords: Organizational behavior; Management